Kapabilitas Pemasaran dan Operasi Serta Pengaruhnya Pada Supply Chain Management dan Kinerja Perusahaan - Hadi Purnomo; Edi Santosa (Jurnal Ekonomi dan Bisnis, 2014)
Competition is a fact that needs to be faced by companies, and competitive advantage is thecore of the company’s success. To face the competition, the accuracy of the strategy undertaken by a company is one of the key success factors of the company. The strategy is to focus on the important factors that affect the performance of the company. In this case, two functions that are key to the creation of value-added are marketing and operations functions. Operations and marketing capabilities are important factors to obtain superior performance. Integration of marketing and operations (operation capabilities, marketing capabilities) is believed to be a synergy to achieve the company's competitive advantage.On the other hand, Supply Chain Management (SCM) is a key strategic factor to improve the company effectiveness. While an effective supply chain process is based on cross-functional collaboration of the company including operations and marketing capabilities. Thus, the main concern of this study is to focus on the influence of operationand marketing capabilities in supply chain integration and the firm performance, as well as the effect of supply chain integration on the firm performance. The results of this study based on regression analysis show that the regression coefficient of each independent variable on the dependent variable is positive. This means that the marketing and operation capabilities have positive effects on the firm performance, as well as having a positive impact on the supply chain integration. On the other side, the supply chain integration also has a positive effect on the firm performance.